A systematic review of outcome measures utilised to assess self-management in clinical trials in patients with chronic pain - Banerjee, Anirban; Hendrick, Paul; Bhattacharjee, Purba; Blake, Holly (Elsevier, 2018)
Objectives The aim of this review was to identify, appraise and synthesise the outcome measures used to assess self-management in patients with chronic pain.